Digital service development strategy in Ganesa Library, SMA Negeri 1 Cangkringan, Yogyakarta - Nur Cahya, Eka Bintang; Wibowo, Setiawan Edi (Universitas Padjadjaran, 2025)
In the current digital era, libraries must develop digital-based services to remain relevant and meet users' increasing demands for fast and easily accessible information. This study investigates the strategic development of digital services at the Ganesa Library, the challenges encountered, and the measures taken to address them. Employing a qualitative research design with a case study approach, data were collected through interviews, observations, and document analysis involving the principal, head of the library, and librarians as key informants. Data validity was ensured through the triangulation of techniques and sources, while data analysis followed the interactive model of Miles and Huberman. The findings indicated that the digital service development strategy comprised three main stages: planning, implementation, and evaluation. The planning phase included needs assessment, goal formulation, feasibility analysis, budgeting, and establishing partnerships. During implementation, the library identifies specific digital services to be developed and delegates operational responsibilities. Evaluation was conducted through the identification of challenges and annual performance reviews. Major challenges faced included limited financial resources, shortage of qualified personnel, inadequate IT skills among librarians, and low utilization of existing digital services. To address these issues, the library organized workshops and seminars that promoted teamwork, encouraged effective communication, and adopted flexible budgeting strategies. These strategic efforts aim to enhance the quality and effectiveness of the Ganesa Library’s digital services, ensuring their continued relevance and responsiveness to users’ needs in the digital age.